Effect of Subcritical Tempering on the Microstructural, Mechanical and Corrosion Behaviour of Mild Steel - Adekunle A. YEKINNI; Adeniyi O. ADESINA; Kazeem A. BELLO (FUDMA Journal of Engineering and Technology, 2025)
Low-carbon steels such as AISI 1018/1020 are widely used in structural and industrial applications due to their low cost, good weldability, and ease of fabrication; however, their limited hardness and susceptibility to corrosion restrict long-term service performance. This study investigates the influence of controlled subcritical tempering on the microstructure, hardness, and corrosion behaviour of commercial mild steel in order to establish clear process–structure–property relationships. Rectangular specimens were normalized at 900 °C for 1 h and subsequently tempered at 500, 550, 600, and 650 °C for 4 h, followed by air cooling. Microstructural evolution was examined using optical microscopy after etching with 2% Nital. Mechanical response was evaluated using Rockwell B hardness testing in accordance with ASTM E18, while corrosion behaviour was assessed through gravimetric immersion testing in 1 N HCl (ASTM G31) and validated using potentiodynamic polarization in 3.5% NaCl solution. The results show that tempering at 500–550 °C promotes pearlite refinement and fine cementite precipitation, leading to a significant increase in hardness, with a maximum value of 270 BHN obtained at 550 °C. However, this condition also exhibited the highest corrosion rate due to increased ferrite–cementite interfacial activity. In contrast, tempering at 600 °C produced a more homogeneous microstructure with reduced galvanic heterogeneity, resulting in the lowest corrosion rate while maintaining moderate hardness. Further tempering at 650 °C caused cementite spheroidization and recovery-dominated softening. The study demonstrates that subcritical tempering provides a viable means of optimizing the mechanical and corrosion performance of mild steel, with 550 °C and 600 °C identified as optimal conditions for strength and corrosion resistance, respectively.
Keywords: Cementite precipitation, Corrosion behaviour, Ferrite–pearlite microstructure, Hardness response, Mild steel, Subcritical tempering.